Hubungan Antara Persepsi Gaya Kepemimpinan Situasional Dan Efektivitas Komunikasi Interpersonal Dengan Komitmen Kerja (Studi Kasus Pada Perawat Di Rumah Sakit Siti Khodijah Sepanjang Sidoarjo Jawa Tengah) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT This research aims to find the relationship between situational leadership style perception, effectiveness of interpersonal communication and job commitment. Hypothesis is postulated that there is the relationship between situational leadership style perceptions, effectiveness of interpersonal communication and job commitment. The subjects of the research were 76 nurses at Siti Khodijah Hospital at Sepanjang Sidoarjo East Java. The data were collected by the means of three questionnaires that is situational leadership style perception questionnaire, effectiveness of interpersonal communication questionnaire and job commitment questionnaires. The data were analyzed by using regression analysis. The result of this research are (1) there was relationship between situational leadership style perception, effectiveness of interpersonal communication and job commitment, (2) there was a relationship between effectiveness of interpersonal communication with the three of job commitment components (affective commitment, continuance commitment, and normative commitment), (3) there was a relationship between the style of telling with affective commitment, continuance commitment, and normative commitment, (4) there was a relationship between the style of selling with affective commitment, and normative commitment, but there was not a relationship with continuance commitment, (5) there was relationship be